Endocrine Disruptors: A Potential Risk Factor for Gestational Diabetes Mellitus - Ehrlich, Shelley; Lambers, Donna; Baccarelli, Andrea; Khoury, Jane; Macaluso, Maurizio; Ho, Shuk-Mei (American Journal of Perinatology, 2016)
Gestational diabetes mellitus (GDM) has increased dramatically in the past 20 years together with the obesity epidemic. Mirroring the increase in incidence of GDM is increasing use of endocrine disrupting chemicals (EDCs). EDCs are structurally similar to endogenous hormones and interfere with synthesis, secretion, activity, or elimination of natural hormones, resulting in adverse health effects, including diabetes, obesity, developmental disorders, etc. Although the association between bisphenol A (BPA), a well-studied EDC, and type 2 diabetes has been repeatedly investigated in epidemiological and animal studies, there is a dearth of studies examining EDCs and GDM. In fact, the impact of environmental toxins on perinatal health outcomes has largely been overlooked.Recognizing this research gap, the American College of Obstetricians and Gynecologists, American Society for Reproductive Medicine, and International Federation of Gynecology and Obstetrics recently joined leading scientists and clinicians in a call for action to prioritize research in the consequences of exposure to toxic environmental agents on women's health. Evidence is emerging to suggest signaling molecules and EDCs are involved in the control of microRNA (miRNA) expression in trophoblast cells. We reviewed existing scientific evidence of EDCs as a risk factor for GDM as well as the potential role of miRNA in this association.
Keywords: gestational diabetes mellitus; endocrine disruptors; miRNA; environmental; epigenetic; biomarkers